1988
DOI: 10.1128/mcb.8.9.3696
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel anti-peptide antibody that recognizes a specific conformation of the platelet-derived growth factor receptor.

Abstract: Two site-specific anti-peptide antibodies (AbPj and AbP2) were raised against the platelet-derived growth factor (PDGF) receptor. These two sites correspond to amino acid residues 977 through 988 (peptide 1) and 932 through 947 (peptide 2) of the murine PDGF receptor. Both antibodies recognized human and murine PDGF receptors in immunoprecipitation and immunoblotting analyses. None of the antibodies was directed to phosphotyrosine. One of the antibodies (AbP2) showed unusual antigen recognition specificity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…Coincident with phosphorylation, PDGF receptor conformation is altered, evidenced by increased accessibility of a cytoplasmic domain epitope for recognition by PDGF receptor peptide antibodies (15,16). One consequence of PDGF receptor self-phosphorylation may be acquisition of a conformation competent to bind and affect function of proteins involved in second messenger generation.…”
mentioning
confidence: 99%
“…Coincident with phosphorylation, PDGF receptor conformation is altered, evidenced by increased accessibility of a cytoplasmic domain epitope for recognition by PDGF receptor peptide antibodies (15,16). One consequence of PDGF receptor self-phosphorylation may be acquisition of a conformation competent to bind and affect function of proteins involved in second messenger generation.…”
mentioning
confidence: 99%
“…gp200 was initially detected by its interaction with an antipeptide IgG, AbP2, directed to a 16-amino-acid peptide epitope in the cytoplasmic domain of the /I-type PDGF receptor. We and others [6, 171 have shown earlier that AbP2 is a novel conformation-specific antibody that recognizes only the tyrosine-phosphorylated PDGF receptor and not the unphosphorylated native receptor; however, it is not directed to phosphotyrosine [6]. In vitro mutagenesis studies have revealed that the P2 epitope is probably involved in mitogenic message transmission [ 191. gp200 neither binds to PDGF nor does it interact with any other anti-peptide IgG to the a-type or 6-type PDGF receptor.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has structural features of a growth-factor receptor, including tyrosine kinase activity, and is recognized by a conformation-specific anti-peptide IgG to the ptype PDGF receptor of 180kDa. This peptide epitope in the unphosphorylated PDGF receptor is cryptic and phosphorylation uncovers this site [6]. Studies conducted with other PDGF-receptor-specific antibodies indicated that gp200 is not an aberrant form of the PDGF receptor.…”
Section: 711)mentioning
confidence: 99%
See 2 more Smart Citations